(untitled) (The Strategic Review for Southern Africa, 2021)
It is widely agreed that service provision is the biggest challenge facing South African municipalities, particularly smaller municipalities. This paper is a South African Municipality document study and focuses on creating a capable state through the developmental government and the effects of these problems in order to find ways to reduce the problems of service delivery. A qualitative approach was used, and data was collected from various jurisdictions through record review and telephone interviews to fill the data gaps in knowledge. Clean water, work prospects and free basic services have been described by most municipalities as the key service delivery obstacles that hinder the realization of a vision for the developmentally competent local government in South Africa. The study found that yet another problem is political intervention in municipal administration. Although public engagement in civic affairs is a legal necessity, much remains to be done to bring about meaningful participation. Sanitation has always been a challenge for service delivery, particularly in rural communities, due primarily to a lack of infrastructure. Lastly, it was found that municipalities need to do more to create human resources to provide services that resemble a status of a developmentally competent South African local government.